IMPLEMENTASI ALGORITMA RIJNDAEL PADA DOKUMEN ELEKTRONIK UNTUK KEAMANAN INFORMASI. - Sifaunajah, Agus (Exact Papers in Compilation (EPiC), 2020)
Cryptography is one of the fields of science in information security. One of the cryptographic algorithms is the Rinjdael algorithm. Security is still not a priority in an information system. The problem that often arises in government data is data leakage. Rinjdael algorithm is implemented to encrypt and decrypt data. The system design uses the waterfall method so that each part can be done optimally. In the trial, the results of the data decryption level that have been done by the encryption process are 100%..